Wetland sulfur isotope signals and dynamic isotope baselines: implications for archaeological research - Wexler, Sarah K.; Stevens, Rhiannon E. (Frontiers in Environmental Archaeology, 2025)
Sulfur isotopic composition (δ34S) is used in archaeological research to reconstruct past mobility patterns and diet using environmental baselines. Human and faunal collagen δ34S is generally interpreted as reflecting environmental baselines derived from geological sulfur and marine sulfur near the coast. However, recent studies have highlighted that the δ34S of bioavailable sulfur is modified in wetlands and waterlogged environments as a result of microbial sulfate reduction and sulfide oxidation. These processes are driven by fluctuating redox conditions resulting from flooding, and can significantly alter bioavailable δ34S baselines in the biosphere, and subsequently in animal tissues, through the food chain. This challenges conventional approaches that assume local geology and coastal proximity alone determine bioavailable baseline δ34S. This study considers sulfur cycling within terrestrial ecosystems and its implications for archaeological interpretation. We explore how plant δ34S is influenced by anoxic soil conditions, hydrological controls and plant waterlogging adaptations, integrating these factors into a theoretical framework and simple numerical models of plant δ34S in wetland and waterlogged environments. The models simulate the effect of different hydrological regimes on plant δ34S (in flow-through, standing water, drained post-flooding, and simultaneously flooded and drained landscapes). We suggest how δ34S could change for crop plants grown using different past water management techniques, and discuss effects of wetland utilization and resource use on animal and human collagen δ34S. This study demonstrates that different systems can result in multiple “wetland” sulfur isotope signals that can deviate both positively and negatively from local baselines that are driven by geological and marine sulfur. δ34S has the potential to be a useful tool for exploring ancient wetland use and water management strategies. Such strategies have long been argued to be critical to early agricultural development and the establishment of complex societies.